ChemInform Abstract: (2S, 5R)‐2‐Methylaminomethyl‐1‐methyl‐5‐phenylpyrrolidine, a Chiral Diamine Ligand for Copper(II)‐Catalyzed Henry Reactions with Superb Enantiocontrol. Issue 36 (9th September 2014) - Scharnagel, Dagmar; Prause, Felix; Kaldun, Johannes; Haase, Robert G.; Breuning, Matthias
Abstract Excellent yields and superb levels of enantiocontrol are achieved in Cu(II)‐catalyzed Henry reactions of aromatic, heteroaromatic, vinylic, and aliphatic aldehydes in the presence of a chiral pyrrolidine ligand derived from L‐pyroglutamate.